1996
DOI: 10.1097/00003246-199610000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of prolonged motor weakness complicating neuromuscular blockade in the intensive care unit

Abstract: The development of motor weakness was associated with an increase in ICU and hospital stays, continued mechanical ventilation, and disproportionate healthcare expenditures in excess of $66,000 per patient. A prospective evaluation of the true prevalence of neuromuscular weakness after neuromuscular blockade and of the costs to the healthcare system is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 23 publications
0
39
0
2
Order By: Relevance
“…44 Aminoglycoside antibiotics were associated with paresis in a single study; however, additional observational studies demonstrated no significant association. 6,34,36,39,40 There are single studies suggesting that other potentially modifiable ICU interventions, including liberal fluid administration and transfusion, journal.publications.chestnet.org may contribute to ICUAW, although these associations need verification in larger patient cohorts. 45,46 Prolonged immobilization is associated with atrophy in patients who are critically ill.…”
Section: In-hospital Risk Factors For Icuawmentioning
confidence: 99%
“…44 Aminoglycoside antibiotics were associated with paresis in a single study; however, additional observational studies demonstrated no significant association. 6,34,36,39,40 There are single studies suggesting that other potentially modifiable ICU interventions, including liberal fluid administration and transfusion, journal.publications.chestnet.org may contribute to ICUAW, although these associations need verification in larger patient cohorts. 45,46 Prolonged immobilization is associated with atrophy in patients who are critically ill.…”
Section: In-hospital Risk Factors For Icuawmentioning
confidence: 99%
“…However, recent prospective and retrospective studies have shown that this is an under-appreciated entity, which is a significant source of morbidity in the ICU, and has significant economic consequences on the usage of health resources. [2][3][4] There is compelling evidence that this syndrome is associated with altered muscle membrane properties and selective loss of myosin and myosin-associated proteins. The altered membrane properties are most probably the primary cause of the absent or very low compound muscle action potentials and the increased amount of spontaneous EMG activity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of protocols based on monitoring of the desired blockade can reduce the mechanical ventilation time, the length of ICU stay and costs. (87,88) 13. Is the use of any specific drug for analgesia and sedation of tetanus patients associated with improved outcomes?…”
Section: Rationalementioning
confidence: 99%